Attraction between like-poles of two magnets mediated by a soft ferromagnetic material - Tarcísio N. Teles; Thiago V.P. de Araújo; Yan Levin (Revista Brasileira de Ensino de Física, 2024)
We present an engaging educational demonstration designed to captivate students’ attention. The experiment reveals an intriguing phenomenon – a surprising attraction between two magnets with identical poles facing each other when a steel metal sphere is inserted between them. Our exploration focuses on both qualitative and quantitative aspects of this magnetic interaction. Specifically, we examine the interaction between two neodymium cylindrical magnets with the like poles facing each other. The experimental setup we introduce allows for the precise measurements of the magnetic force between the magnets. To gain a quantitative understanding of our measurements, we employ electromagnetic theory. This theoretical framework allows us to determine the magnetic energy within the system and to easily calculate the force between the magnets.